2018
DOI: 10.1136/sextrans-2017-053346
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiota composition and association with prevalent Chlamydia trachomatis infection: a cross-sectional study of young women attending a STI clinic in France

Abstract: ObjectivesNew molecular techniques have allowed describing groups of bacterial communities in the vagina (community state types (CST)) that could play an important role in Chlamydia trachomatis (CT) infection. Our aim was to describe the distribution of CST in a population of young women in France.MethodsA cross-sectional study was carried out in June 2015 among anonymous young women attending a STI clinic in Bordeaux, France. Participants provided a vaginal sample for CT screening and sociodemographic data. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 11 publications
0
50
1
Order By: Relevance
“…Several genera were more abundant among samples of women with CT included Collinsella and Dialister compared to controls and Anaerococcus and Corynebacterium compared to TV (Fig 4). We could not confirm the finding of Tamarelle et al [27], who reported that infection with CT was associated with vaginal microbiomes dominated by Lactobacillus iners and largely lacking other Lactobacillus species respectively with a wide array of strict and facultative anaerobes.…”
Section: Discussioncontrasting
confidence: 99%
“…Several genera were more abundant among samples of women with CT included Collinsella and Dialister compared to controls and Anaerococcus and Corynebacterium compared to TV (Fig 4). We could not confirm the finding of Tamarelle et al [27], who reported that infection with CT was associated with vaginal microbiomes dominated by Lactobacillus iners and largely lacking other Lactobacillus species respectively with a wide array of strict and facultative anaerobes.…”
Section: Discussioncontrasting
confidence: 99%
“…The classification of vaginal microbial communities into community state types has proven to be highly valuable. Since their inception in 2011 [7], studies have shown associations between vaginal CSTs and host immune profiles [25] and have further linked particular CSTs to sexually transmitted infections [18,21,27] and experiencing spontaneous preterm birth [8,40,41]. From these studies it is clear that the CST classification system captures meaningful information about these communities, despite its apparent simplicity.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of CSTs was introduced in 2011 by Ravel et al to categorize vaginal microbial communities routinely observed among reproductive age women [7], and built upon prior methods to categorize these communities [16]. That study, and many subsequent studies [7,[17][18][19][20][21], have indicated that there are at least five vaginal CSTs, four of which are each dominated by different Lactobacillus spp. and another characterized by a more even community of facultative and obligate anaerobic bacteria (some studies have also distinguished subtypes within this CST [22]).…”
mentioning
confidence: 99%
“…With the advent of high-throughput sequencing methods, more and more studies have proposed 16S rRNA sequencing to estimate the composition of vaginal microbiome. (1517) Partial amplification of bacterial 16S gene sequences with primers across hypervariable regions, mainly including V1-V2 region(15, 18) and V3-V4 region,(17, 19, 20) is a common method to describe vaginal bacterial populations. However, it has been shown that different selection of primers for amplification can bias the results of 16S amplicons for microbiome studies.…”
Section: Introductionmentioning
confidence: 99%